Sustainability impact assessment tools and frameworks - Mulligan, Catherine N. (Frontiers in Environmental Engineering, 2026)
Global challenges are increasing for the design of sustainable infrastructure and buildings for engineers. These include resource constraints and limited availability of water. Climate change from increasing greenhouse gas emissions is changing precipitation patterns, putting further constraints on resources. Incorporating sustainable practices into infrastructure projects is becoming increasingly important. However, there are many challenges related to this. Tools and frameworks for sustainability impact assessments have been developed to assist in the decision-making process. Environmental and economic indicators are well developed but social aspects are more difficult to quantify. This paper examines selected tools and frameworks and the requirement for future developments. Sustainability in engineering design is essential for working towards the UN Sustainability Development Goals.